The Influence of Living Qur’an of the Formation of Generation Z’s Religious Identity - Kuliyatun; Teguh Luhuringbudi; Panggih Abdiguno; Yahya Komarudin; Dewi Nita Utami; Mowafg Abrahem Masuwd (Tunjuk Ajar: Journal of Education and Culture, 2025)
This study sets out to examine the influence of the Living Qur'an on the formation of Generation Z's religious identity, focusing on how these teachings are internalised through social interactions. The main objective of the study was to explore the relationship between religious activities and religious identity among the younger generation. Data were collected through a questionnaire distributed to 203 respondents, consisting of various educational backgrounds. The analytical methods employed included Social Identity Theory, Symbolic Interaction Theory, and Theory of Religious Socialization, which provided an in-depth perspective on the findings. The results indicated that 55.7% of respondents regarded religious activities in madrasahs as having a very strong influence on their daily lives.This study offers novel insights into Islamic studies, underscoring the significance of contextual religious education that fosters active participation. The study's limitations, which include a limited sample size, are discussed, and suggestions for future research are provided, including a broader exploration of social and technological factors in the formation of religious identity in the modern era.